Islamic Coins and Their Importance in the Study of Islamic History and Archaeology. - شعفور ضياء الدين; غادة حسن; شيرين حمودة (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
This study included Islamic money, its cultural role and history, and included the science of coins or money. It shed light on the importance of the invention of money, clarified the presence of currency in Islamic sources, showed the types of currency used and the manufacture of money, touched on the counterfeiting and adulteration of currency and the motives behind these fraudulent operations, and mentioned the types of counterfeit money... Importance of the Research:The significance of this study lies in providing a clear picture of coins and their role in facilitating transactions. It emphasizes the importance of coins and the history of their development, outlining the stages of coin manufacturing and illustrating the patterns of currency, such as dinars, dirhams, and fals. It also discusses methods of counterfeiting and forgery, as well as the reasons behind the resort to currency fraud. Research Problem: This research aims to shed light on coins and their importance in studying history, as coins contribute to enriching historical knowledge in both ancient and modern countries, especially when documents become silent and unable to express or convey information. The research revolves around several important questions: What is the significance of coins in the study of history? What are the main categories of currency, and what is the role of money in Islamic sources? What are the reasons or motivations for using forgery and counterfeiting methods in currency? Conclusion: From the above, we can see that the importance of this research lies in the information it provides about coins, their types, methods of coin production, and their role in historical studies. It helps to fill the gaps that sometimes arise due to the loss of documents during certain historical periods. Thus, coins serve as the element that completes some parts of historical deficiency, and the invention of coins is a significant historical event, no less important than the invention of writing.